A Randomised Clinical Control Study to Evaluate the Efficacy of Shodhita Kuchla Powder (Purified Strychnos Nux-Vomica L.) and Brahmi Extract (Bacopa Monnieri L. Pennell) on Klaibya (Dhwajbhang) w.s.r. to Erectile Dysfunction - Deepak Verma; Ashwini Kumar Sharma; Megha Shukla (AYUSHDHARA, 2021)
Klaibya is defined in Ayurveda as the inability to achieve and maintain sufficient rigidity in the penis, which is essential for his sexual urges or the needs of his female partner during sexual activity. Chakrapani limits the concept of Klaibya to merely erectile dysfunction. Dhwajbhang, according to Acharya Sushruta, is a form of Klaibya caused by excessive coitus. The standard initial evaluation of a man experiencing ED is conducted in person and involves sexual, medical, and psychosocial histories, as well as laboratory tests comprehensive enough to identify comorbid diseases that may predispose the patient to ED and may contraindicate particular treatments. Properties of Ayurvedic drug; Kuchla (Strychnos nux-vomica) in classical text Rasatarangani as therapeutic of Klaibya (ED) and Brahmi (Bacopa monnieri) is well known Medhya drug that works on neuro- psychological disorders. The current study evaluated the effects of Kuchla and Brahmi on 36 erectile dysfunction patients, having 30 of them completing the trial. The patients were categorized into two parts: Group A administered an ED 250 capsule (Hypothetical) once a day (250mg) with milk, and Group B received a placebo once a day with milk HS for 30 days, followed by another 30 days.